2013
DOI: 10.1016/j.cell.2013.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Cristae Shape Determines Respiratory Chain Supercomplexes Assembly and Respiratory Efficiency

Abstract: SummaryRespiratory chain complexes assemble into functional quaternary structures called supercomplexes (RCS) within the folds of the inner mitochondrial membrane, or cristae. Here, we investigate the relationship between respiratory function and mitochondrial ultrastructure and provide evidence that cristae shape determines the assembly and stability of RCS and hence mitochondrial respiratory efficiency. Genetic and apoptotic manipulations of cristae structure affect assembly and activity of RCS in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
939
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,040 publications
(999 citation statements)
references
References 50 publications
52
939
4
4
Order By: Relevance
“…Instead, our data suggest that a late defect in complex I may account for the reduction of electron transport across the respiratory chain as evidenced by the decreased maximal respiration in mutant neurons and the reduction of complex I levels and activity. Functional changes in complex I were previously reported in fibroblasts with OPA1 haploinsufficiency18 or the p.G488R mutation9 and in models of acute OPA1 depletion, where respiratory efficiency was impaired when mitochondria were energized specifically with the complex I substrates, glutamate/malate 17. Therefore, in human iPSC‐derived neurons, OPA1 levels are important for the maintenance of oxidative phosphorylation, at least partly, by regulating the stability of complex I.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, our data suggest that a late defect in complex I may account for the reduction of electron transport across the respiratory chain as evidenced by the decreased maximal respiration in mutant neurons and the reduction of complex I levels and activity. Functional changes in complex I were previously reported in fibroblasts with OPA1 haploinsufficiency18 or the p.G488R mutation9 and in models of acute OPA1 depletion, where respiratory efficiency was impaired when mitochondria were energized specifically with the complex I substrates, glutamate/malate 17. Therefore, in human iPSC‐derived neurons, OPA1 levels are important for the maintenance of oxidative phosphorylation, at least partly, by regulating the stability of complex I.…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondrial cristae morphology also influences respiratory chain organization. 40,49 GB disrupts cristae junctions through an unknown mechanism, which likely contributes to mitochondrial dysfunction and ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Cristae morphology is a critical determinant of ETC organization and respiratory efficiency. 40 We therefore examined whether GB treatment might also affect the shape of cristae. By electron microscopy, we observed that in GB-treated mitochondria many of the cristae appeared to have lost their junction (Figures 6h and i).…”
Section: Gb-induced Ros Requires a Functional Respiratory Chainmentioning
confidence: 99%
“…The inner membrane dynamin-like GTPase Opa1 mediates inner membrane mitochondrial fusion and morphology (13,15,16). Inner membrane proteases such as Oma1 cleave long membrane-bound Opa1 forms (Opa1-L) into short soluble forms (Opa1-S).…”
Section: Journal Of Biological Chemistry 24883mentioning
confidence: 99%